Utilization of a public subsidy scheme for dental care services among socially vulnerable citizens out of labor in Copenhagen, Denmark - Marie Skov Kristensen; Annette Kjær Ersbøll; Ingelise Andersen; Esben Boeskov Øzhayat (Medical Journals Sweden, 2024)
Objective: Addressing social inequality in oral health and access to dental care is a global concern. This study aims to describe the utilization of a public subsidy scheme targeting vulnerable individuals out of labor in Copenhagen municipality (2013-2018) and to identify key characteristics of individuals eligible to apply. Material and Methods: Data from Copenhagen municipality were combined with data from population and health registers. Employing logistic regression analyses, we examined the association between demographic, socioeconomic, and health-related characteristics and (1) having applied, (2) being granted, and (3) using the subsidy. Results: The study included 65,174 individuals aged 18-65. Of these 10,369 (15.9%) applied for subsidies, submitting a total of 18,529 applications. Overall, 83% of the applications were granted and 85% were used. Significantly increased odds of applying for subsidies were observed among individuals receiving social benefits non-stop over the past year versus none (odds ratio [OR] = 15.45, 95% confidence interval [CI] = 14.24-16.76), aged 50-65 versus 18-29 years (OR = 4.41, CI= 4.15-4.69), and having combined indicators of social vulnerability versus none (OR = 2.90, CI= 2.73-3.07). Conclusions: While the utilization of the public subsidy scheme is low, individuals who apply are likely to be granted a subsidy and use it. Vulnerability was associated with greater utilization of the scheme, yet a substantial portion of those at risk of poor oral health did not take advantage of it.